2009
DOI: 10.1371/journal.pgen.1000465
|View full text |Cite
|
Sign up to set email alerts
|

Buffering of Segmental and Chromosomal Aneuploidies in Drosophila melanogaster

Abstract: Chromosomal instability, which involves the deletion and duplication of chromosomes or chromosome parts, is a common feature of cancers, and deficiency screens are commonly used to detect genes involved in various biological pathways. However, despite their importance, the effects of deficiencies, duplications, and chromosome losses on the regulation of whole chromosomes and large chromosome domains are largely unknown. Therefore, to explore these effects, we examined expression patterns of genes in several Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
132
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 30 publications
18
132
1
Order By: Relevance
“…Although X-linked gene expression is significantly increased, the overall increase is far less than expected of two active X chromosomes. These data thereby provide support for inherent genome balance and "inverse effects" as historically observed in plants and flies (Stenberg et al 2009;Birchler 2013;Sun et al 2013). However, they also demonstrate that small deviations from X-autosomal equivalence can have a major impact on survival and fitness.…”
supporting
confidence: 66%
“…Although X-linked gene expression is significantly increased, the overall increase is far less than expected of two active X chromosomes. These data thereby provide support for inherent genome balance and "inverse effects" as historically observed in plants and flies (Stenberg et al 2009;Birchler 2013;Sun et al 2013). However, they also demonstrate that small deviations from X-autosomal equivalence can have a major impact on survival and fitness.…”
supporting
confidence: 66%
“…Interestingly, the expression level for most of the studied genes showed tissue-specific differences in response to aneuploidy. Only recently, global gene expression profiling studies have been performed in aneuploid tissues from human and mouse (Mao et al, 2003(Mao et al, , 2005Kahlem et al, 2004;Lyle et al, 2004;FitzPatrick, 2005;Ait Yahya-Graison et al, 2007;Laffaire et al, 2009), Drosophila flies (Stenberg et al, 2009), Arabidopsis (Arabidopsis thaliana; Huettel et al, 2008), and maize seedlings (Makarevitch et al, 2008). Several models explaining the effects of aneuploidy on global gene expression have been proposed FitzPatrick, 2005;Birchler and Veitia, 2007).…”
mentioning
confidence: 99%
“…Such a response in trans can lead to large quantitative differences in gene expression (up-regulation as well as down-regulation) or even qualitative changes in gene expression patterns and affect many genes due to complex gene interactions. All of the studies assaying global gene expression in aneuploids reported trans-effects as well as some level of functional gene dosage compensation, or a "buffering" effect, when the level of RNA transcript read from genes present in three copies due to segmental aneuploidy were found to be similar to wild-type levels (Mao et al, 2003(Mao et al, , 2005Kahlem et al, 2004;Lyle et al, 2004;FitzPatrick, 2005;Potier et al, 2006;Ait Yahya-Graison et al, 2007;Huettel et al, 2008;Makarevitch et al, 2008;Moldrich et al, 2009;Stenberg et al, 2009). The degree of reported dosage compensation varied substantially between studies: from 3% to 15% in Arabidopsis (Huettel et al, 2008) and developing human brain cells (Mao et al, 2003(Mao et al, , 2005 to over 65% in human lymphoblastoid cells (Ait Yahya-Graison et al, 2007).…”
mentioning
confidence: 99%
“…Similarly, microarray analysis of mRNA levels revealed a gene-dosage dependent increase of mRNA levels of genes encoded on the extra chromosomes, as well as other deregulations, but no specific expression pattern in these trisomic MEFs [39]. Analysis of transcriptional data from Drosophila cells with various segmental and chromosomal aneuploidies identified no general response to the chromosome number changes [45,46]. Thus, further research will be required to address the question whether all eukaryotic cells show a unified response to aneuploidy, or whether this is something to be observed only in budding yeast.…”
Section: Global Response To Aneuploidymentioning
confidence: 99%
“…Using Drosophila as another excellent model for analysis of the effects of aneuploidy, recent research revealed a significant buffering of genes in aneuploid regions [45,46]. The authors also identified that the buffering is more efficient for differentially expressed genes than for genes that are expressed ubiquitously.…”
Section: Protein Homeostasis In Aneuploidsmentioning
confidence: 99%